Economic evaluation in genomic and precision medicine - Mitropoulou, Christina; Wordsworth, Sarah; Buchanan, James; Patrinos, George P. (Translational and applied genomics series., 2023)
Economic Evaluation in Genomic and Precision Medicine provides an in-depth examination of essential concepts, protocols and applications of economic evaluation in genomic and precision medicine. Contributions from leading international medical geneticists and health economists compile new ways to effectively assess the costs and outcomes of different genomic care pathways, implement cost-effective medical interventions, and enhance the value of genomic and precision healthcare. Foundational chapters and discipline-specific case studies cover topics ranging from the economic analysis of genomic trial design, to health technology assessment of next-generation sequencing, ethical aspects, economic policy in genomic medicine, and pricing and reimbursement in clinical genomics.